ANALYSIS OF FIQH MUAMALAH AND FATWA DSN MUI NO. 145 OF 2021 ON THE PRACTICE OF ONLINE DROPSHIPPING IN THE CITY OF BANDA ACEH, INDONESIA - Iskandar, Teuku Agam (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2024)
The majority of scholars are of the opinion that the practice of dropship is haram because of this form of buying and selling, where the goods sold do not belong to the drop shipper (seller). This research aims to find out about the law of online drop shipping according to DSN-MUI Fatwa No.145 of 2021. This research uses the juridical-normative method, where the main data is obtained from a number of laws and regulations, fatwas of scholars and other secondary data. The results show that drop shipping is permissible as long as it does not conflict with the provisions of Islamic law: first, the drop shipper must first buy goods from the supplier before the goods are sold to the buyer; second, the drop shipper and the supplier have worked together so that the drop shipper has been authorized to sell the goods; third, there is a sighat ijab-kabul or contract that has been regulated in the fatwa; fourth, there is clarity about the goods, both in form, quality, cost and delivery time; fifth, there is a dispute resolution mechanism between drop shipper, supplier and consumer.